2005
DOI: 10.1007/s00421-004-1311-2
|View full text |Cite
|
Sign up to set email alerts
|

RPE-lactate dissociation during extended cycling

Abstract: This study examined the association of blood lactate concentration [La] and heart rate (HR) with ratings of perceived exertion (RPE) during 60 min of steady workload cycling. Physically active college-aged subjects (n = 14) completed an exhaustive cycling test to determine VO(2) (peak) and lactate threshold (2.5 mmol l(-1)). Subjects then cycled for 60 min at the power output associated with 2.5 mmol l(-1) [LA]. HR, [LA], RPE-overall, RPE-legs and RPE-chest were recorded at 5, 10, 20, 30, 40, 50 and 60 min. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
2
27
1
5
Order By: Relevance
“…In contrast, Green et al (2005) found dissociation between LA and RPE, when 14 physically active men and women were tested during extended cycling exercise. They reported that HR and RPE responses were similar but not RPE and LA.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, Green et al (2005) found dissociation between LA and RPE, when 14 physically active men and women were tested during extended cycling exercise. They reported that HR and RPE responses were similar but not RPE and LA.…”
Section: Discussionmentioning
confidence: 57%
“…Utilizando la escala de Borg original (25), López-Miñarro y MuyorRodriguez (3) observaron puntuaciones que indicaban una intensidad entre "duro -muy duro", similares a las puntuaciones obtenidas en nuestro estudio. Algunas variables no examinadas podrían haber afectado sobre el comportamiento de la RPE como el tipo de entrenamiento (26,27), la música (28-31) o la cadencia de pedaleo (32).…”
Section: Discussionunclassified
“…López-Miñaro y Muyor-Rodriguez (3) obtuvieron similares correlaciones entre la RPE y el %FCR (r=0.41; p<0.05) en una sesión de ciclismo indoor, al igual que otros estudios realizados sobre cicloergómetro, aunque no durante la práctica de ciclismo indoor (26,33). Las correlaciones observadas en nuestro estudio entre FC -RPE y entre %FCmáx teórica -RPE fueron similares.…”
Section: Discussionunclassified
“…25 Consequently, there is considerable interest in lactate biosensors, but despite substantial body of research, the relatively poor stability of L-lactate oxidase (LOx) limits the effectiveness of current devices. 26,27 LOx is a flavin mononucleotide (FMN) enzyme that catalyzes the oxidation of L-lactic acid into pyruvate, producing H 2 O 2 in the process.…”
Section: Introductionmentioning
confidence: 99%